Network neutrality : From policy to law to regulation - Marsden, Christopher T. (Manchester University Press, 2017)
"This study explains the concept of network neutrality and its history as an extension of the rights and duties of common carriers, as well as its policy history as examined in US and European regulatory proceedings from 1999. The book compares national and regional legislation and regulation of net neutrality from an interdisciplinary and international perspective. It also examines the future of net neutrality battles in Europe, the United States and in developing countries such as India and Brazil, and explores the case studies of Specialized Services and Content Delivery Networks for video over the Internet, and zero rating or sponsored data plans. Finally, Network neutrality offers co-regulatory solutions based on FRAND and non-exclusivity. This is a must-read for researchers and advocates in net neutrality debate, and those interested in the context of communications regulation, law and economic regulation, human rights discourse and policy, and the impact of science and engineering on policy and governance."